Ruth Davidson's Conservatives : the Scottish Tory Party, 2011-19 - Torrance, David (Edinburgh University Press, 2020)
This book, which brings together leading academics and analysts, examines the extraordinary revival of the Scottish Conservative Party between 2011 and Ruth Davidson's shock resignation in 2019.